The effect of black mulberry (Morus nigra) extract on carbon tetrachloride-induced liver damage - Deniz, Gulsah Yildiz; Laloglu, Esra; Koc, Kubra; Nadaroglu, Hayrunnisa; Geyikoglu, Fatime (Archives of Biological Sciences, 2018)
In this study, the effect of Morus nigra (M. nigra) on carbon tetrachloride (CCI4)-induced hepatic injury in the rat was investigated. A hepatotoxic rat model was developed by the injection of CCI4 dissolved in soybean oil (1 mL/kg/twice a week, intraperitoneal (i.p.) injection). Following the formation of hepatic injury, extracts of M. nigra at doses ranging from 150 to 300 mg/kg were administered to rats by i.p. injection for eight weeks. At the end of administration, rat livers were excised by dissection. The activities of liver enzymes, alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyl transferase (GGT) were detected in the serum, and the activities of antioxidant enzymes, superoxide dismutase (SOD) and glutathione peroxidase (GPx), were established in the liver. Histological changes and immunohistochemical localization of caspase-3 and 8-oxo-2'-deoxyguanosine (8-OhdG) were performed by hematoxylin-eosin (H&E) staining of liver sections and caspase-3 and 8-OhdG immunohistochemical staining. The results showed that the M. nigra extract prevented protein oxidation generated by CCI4. The extracts demonstrated the ability to modulate the activity of SOD and GPx, and also prevented the CCI4-induced increase in AST and GGT levels. These results indicate that M. nigra extracts provided significant protection against CCl4-induced hepatic injury and might also present a novel approach for the treatment of some liver diseases. https://doi.org/10.2298/ABS171009055D Received: October 9, 2017; Revised: December 6, 2017; Accepted: December 12, 2017; Published online: December 22, 2017 How to cite this article: Deniz GY, Laloglu E, Koc K, Nadaroglu H, Geyikoglu F. The effect of black mulberry (Morus nigra) extract on carbon tetrachloride-induced liver damage. Arch Biol Sci. 2018;70(2):371-8.